In-vivo analysis of nerve regeneration after sciatic nerve injury in a rat model. Issue 1 (1st January 2016) - Hansen, Clint; Dinis, Tony M.; Vidal, Guillaume; Ben-Mansour, Khalil; Bresson, Damien; Egles, Christophe; Marin, Frédéric
Abstract: We investigated the effectiveness of artificial silk-based nerve graft in nerve recovery and in helping regain motor functionality in rats. The purpose of this study is to test two questions: (1) Can nerve growth after transection be improved using artificial nerve guides? (2) Does nerve recovery have an impact on the walking patterns of the rat during the recovery period? Rats underwent sciatic nerve sectioning followed by reconstructive surgery. In these experiments, the sciatic nerve was substituted with an artificial silk guide that was biofunctionalized with growth factors and tested in vitro, as described previously. Three-dimensional motion capture and histological analyses were performed. After recovery periods of three and six months, the rats' kinematics were analyzed during an over-ground walking task to evaluate the nerve recovery progress. The functional nerve recovery showed significant differences between the operated and non-operated sides of the rat, but no differences in their walking patterns during the recovery period. The histological analysis showed the reorganization of nerve tissue into the nerve as well as the presence of multiple neuronal extensions. Here, we have shown histological improvement in the absence of functional restoration after sciatic nerve transection and reconstruction at six months.